2013
DOI: 10.1002/mnfr.201300526
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and cancer risk, epidemiological evidence, and molecular mechanisms

Abstract: Although early studies suggested that coffee consumption might increase risk of some cancers, more comprehensive epidemiological and experimental data now generally indicate either neutral or beneficial effects. In this review, we summarize the current evidence for associations between breast, prostate, colorectal, and liver cancers and the consumption of coffee, and discuss the experimental evidence for potential chemopreventive mechanisms of coffee and coffee constituents. The epidemiological evidence consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 130 publications
2
105
1
11
Order By: Relevance
“…Previous epidemiological studies indicated that coffee consumption is associated with a protective effect for colorectal cancer with a relative risk of 0.83 (95% confidence interval: 0.75-0.92) in a previous meta-analysis (27,28). The inhibitory effect of coffee extract on KRAS expression may be a key factor underlying the protective effects of coffee against colorectal cancer.…”
Section: Discussionmentioning
confidence: 90%
“…Previous epidemiological studies indicated that coffee consumption is associated with a protective effect for colorectal cancer with a relative risk of 0.83 (95% confidence interval: 0.75-0.92) in a previous meta-analysis (27,28). The inhibitory effect of coffee extract on KRAS expression may be a key factor underlying the protective effects of coffee against colorectal cancer.…”
Section: Discussionmentioning
confidence: 90%
“…Studies revealed that all coffee extracts decreased ROS generation by 28.6-61.0% compared to the control and by 59.1-77.8% compared to cells with induced oxidative stress. The results suggest that coffee extracts decreased the level of ROS even in cells representing physiological amounts of ROS due to their high scavenging and oxidative stress inhibition activities [34,35]. The higher activity to decrease ROS generation showed DiRCE.…”
Section: Effect Of Coffee Extracts On Viability and Level Of Intracelmentioning
confidence: 99%
“…The extract of roasted coffee, particularly the fraction containing monochlorogenic acids and more polar MRP, caused an increase of antioxidant potential evaluated as high radical-scavenging capacity and a high level of hydrophilic antioxidants in rat serum and may be potentially used as a nutraceutical of anticarcinogenic properties due to inhibition of oxidative stress resulting from the antioxidant capacity [34]. The results related to the antidiabetic activity of coffee, including protection against oxidative stress of β cells and the low levels of triglycerides, glucose and oxidized glutathione levels in rats, showed a beneficial effect of non-fractionated GCE.…”
Section: Animal Studymentioning
confidence: 99%
“…chlorogenic acid, polyphenols and their metabolites). 47 Coffee constituents may have antioxidant properties, play a role in the regulation of DNA repair, apoptosis and inflammation, 47 have effects on hormonal activity, [48][49][50] glucose tolerance 51 and circulating levels of immune and inflammatory markers. 52 …”
Section: Coffeementioning
confidence: 99%